Physicochemical characterization of Jatropha podagrica seed oil for potential biodiesel production and other industrial applications in Thailand - Duangporn Premjet,; Obeng, Abraham Kusi; Hah, Young Yoo; Seung, Wook Kim; Siripong Premjet, (Penerbit Universiti Kebangsaan Malaysia, 2021)
Jatropha is considered as one of the most promising potential oil sources for biodiesel production and other industrial applications. However, research on the potential of Jatropha seed oil is mainly focused on Jatropha curcas, with other species receiving little attention. The physicochemical properties of J. podagrica seed oil was studied to determine its potential as feedstock for biodiesel production and other industrial applications in Thailand. The seed oil was extracted with n-hexane from milled kernels using the soxhlet extractor and subsequently characterised for free fatty acids, iodine value, viscosity, saponification value, density, and acid value. The fatty acid profile of the seed oil was also analysed using gas chromatography (GC). Analysis of the physical properties of the J. podagrica seed kernel showed lower average physical characteristics when compared to those of J. curcas seed kernel. J. podagrica seeds had high oil content comparable to J. curcas oil content. The main fatty acid components of the seed oil were oleic acid (15%) and linoleic acid (70%). Generally, the results of the physicochemical analysis indicated that J. podagrica seed oil would be very useful for the production of soap and shampoo in Thailand. To produce biodiesel from the seed oil, a two-step acid-catalysed transesterification process would be appropriate.